One CGIAR Consultation Workshop on ‘Digital Innovation and Transformation in Food-Water-Land Systems in India' - Singaraju, Niyati; Puskur, Ranjitha; Gartaula, Hom Nath; Sharma, Sheetal (International Rice Research Institute, 2022)
Under its new research for development (R4D) initiative on digital innovation and transformation, the Consultative Group on International Agriculture Research (CGIAR), organised a two-day workshop on 8 and 9 November 2022, at Bhubaneswar, Odisha, India. The workshop was aimed to better understand the actor landscape of the digital ecosystem in food-water-land systems. This includes: the availability, accessibility, gender responsiveness and effectiveness of services; the challenges and opportunities in promoting an inclusive, gender-intentional and beneficial digital ecosystem; and the data management challenges associated with data security and governance. Essential stakeholders encompassing representatives from government, research, private, producer and Non-Governmental Organizations having expertise and experience in digital innovations participated in the workshop.